Membangun Karakter Hemat dan Cerdas Finansial Melalui Pendidikan Literasi Keuangan di SDN 040459 - Syahira, Nazwa; Laily Azizah, Zhulfi; Purba, M Nabil Hanifah; Hidayatullah, Rahman; Siregar, Lailatun Nur Kamilah (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service aims to improve students' thrifty character and financial intelligence through financial literacy education at SDN 040459 Berastagi. The community service implementation method uses the Kemmis and McTaggart participatory action approach model which is implemented in two cycles, including planning, action, observation, and reflection stages. The target of the activity is 55 students in grades VI A and VI B. Data collection techniques are carried out through financial literacy tests and observations of student behavior. The results show an increase in students' financial literacy from the pre-action stage by 55% to 67% in cycle I, and increased again to 75% in cycle II. Significant improvements are also seen in indicators of the ability to distinguish needs and wants (45% to 85%), saving habits (35% to 78%), planning the use of pocket money (35% to 70%), and recording simple expenses (25% to 65%). Thus, financial literacy education based on interactive learning and direct practice has proven effective in building thrifty character and financial intelligence in elementary school students.